PAI Teacher Qualification Standards as the Main Pillar in Islamic Character Education - Mokhamad Taufik; Mohamad Nur Kholis Setiawan; Muehammad Eka Mahmud (Universitas Muhammadiyah Palu, 2024)
The Qualification Standards for Islamic Religious Education (PAI) Teachers play a crucial role in the development of Islamic character education in Indonesia. This study aims to analyze how the qualification standards for PAI teachers can be the main pillar in shaping the character of students. Through a qualitative approach, this study identifies the competencies required by PAI teachers, including academic knowledge, pedagogical skills, and moral values ??that are in line with Islamic teachings. The results of the study indicate that improving the qualifications of PAI teachers not only affects the quality of teaching, but also the formation of student character that reflects noble morals. Thus, the development of PAI teacher qualification standards is a strategic step in realizing sustainable and effective Islamic character education. This study is expected to be a reference for policy makers and educational institutions in improving the quality of religious education in Indonesia